2012
DOI: 10.1159/000333553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in the Use of Cephalosporins in Pediatric Patients with a History of Penicillin Allergy

Abstract: Background: The risk of cephalosporin administration in patients with a history of penicillin allergy is unclear. Few studies have looked at the risk of cephalosporin administration in children following penicillin skin testing for suspected penicillin allergy. The goal of this study was to determine whether children with penicillin allergy were at increased risk for adverse drug reactions when administered a cephalosporin. Methods: A retrospective chart review was conducted in pediatric patients (≤18 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…More recent studies have shown that the rate of cross-reactivity between penicillins and cephalosporins is much lower than concluded in earlier studies. 35,40,67 71 One of these studies was prospective in nature, which confirmed penicillin allergy by skin test and 41 patients were treated with cefazolin, cefuroxime, or ceftriaxone and no patients had an allergic reaction. This study concluded that cross-reactivity is low, provided that the side chain is different than that of the penicillin responsible for the allergic reaction.…”
Section: Cephalosporin Cross-reactivitymentioning
confidence: 94%
“…More recent studies have shown that the rate of cross-reactivity between penicillins and cephalosporins is much lower than concluded in earlier studies. 35,40,67 71 One of these studies was prospective in nature, which confirmed penicillin allergy by skin test and 41 patients were treated with cefazolin, cefuroxime, or ceftriaxone and no patients had an allergic reaction. This study concluded that cross-reactivity is low, provided that the side chain is different than that of the penicillin responsible for the allergic reaction.…”
Section: Cephalosporin Cross-reactivitymentioning
confidence: 94%
“…However, one (0.7%) of the 152 patients with negative skin test had an immediate allergic reaction after cephalexin, underscoring the lack of predictive power of the penicillin skin test. 50 In a meta-analysis by Pichichero 15 There was a trend towards increased risk for firstgeneration cephalosporins, although the result did not reach statistical significance.…”
Section: Clinical Reaction To Cephalosporins In Patients With Penicilmentioning
confidence: 99%
“…None developed crossreactivity. 49 Ahmed et al 50 reviewed 173 children with a history of penicillin hypersensitivity, with or without a skin test, who underwent cephalosporin challenge. None among those with positive skin test showed reactivity.…”
Section: Clinical Reaction To Cephalosporins In Patients With Penicilmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these false data have populated medical practice, resulting in the propagation of the 10% cross-allergy myth across decades. In contrast, more careful recent studies demonstrate clinically significant immunologically mediated cross-reactivity of <1% [63][64][65][66][67]. These low rates have been incorporated into guidelines within the anaphylaxis practice parameter.…”
Section: Alternative β-Lactam Options: Cross-allergies Across the β-Lmentioning
confidence: 99%